P562 Treatment of older inflammatory bowel disease patients; steroid use and escalation to steroid sparing therapy. (25th January 2019) - Asscher, V; Provoost, N; Meijer, L; van der Meulen-de Jong, A; van Deudekom, F; Mooijaart, S; Maljaars, J
Abstract: Background: Steroid therapy is essential in treatment of IBD. However, both prednisone and budesonide are not effective in maintaining remission and associated with systemic side effects. Therefore, more than one steroid course per year is a threshold for escalation to steroid-sparing therapy in all age groups. Nevertheless, medical treatment of older patients with IBD is often not optimised. The aim of this study was to assess steroid use and escalation rates in older IBD patients in an academic centre in the Netherlands. Methods: Consecutive IBD patients (CD, UC and IBD-U) were included at the outpatient department of a university hospital. Disease activity was assessed through HBI or PMS (remission: HBI <5 or PMS <2), steroid use (oral prednisone and oral budesonide) was classified per year for the last 3 years (no steroid use, steroid use < 14 (1 course) or 15–52 weeks (more than one course)). Steroid sparing therapy was defined as the introduction or use of immunomodulators/biologicals. Adherence to treatment escalation guidelines (prednisone) and adjusted treatment escalation guidelines (prednisone and budesonide) was present when steroid sparing therapy was introduced after >1 course of steroids. Fisher exact test and binary logistic regression were used, a P value of <0.05 was considered statistically significant. Results: 355 patients were included: 197 patients aged ≥65 years and 158 patients aged <65 years (mean age 70.82 (SD 4.59) vs. 40.85 (SD 13.36); 54.8% vs. 41.8% male ( p = 0.019), 50.8% vs. 69.0% CD ( p = 0.001); 76.7% vs. 76.0% remission ( p = 0.899)). Older patients were less likely to receive steroids over the past 3 years (29.1% vs. 48.8%, p = 0.000) and to currently receive steroid sparing agents (36.0% vs. 65.6%, p = 0.000). No difference was observed in adherence to treatment escalation guidelines (87.5% vs. 100%, p = 0.444), but older patients were less likely to be treated according to adjusted treatment escalation guidelines (59.5% vs. 85.7%, p = 0.011). Age, corrected for sex and IBD type, was an independent predictor for non-adherence to adjusted treatment escalation guidelines (age category ≥70; OR 5.598, 95% CI 1.201–26.087). Conclusions: IBD patients aged ≥65 years had a lower rate of both steroid and steroid sparing therapy use compared with younger patients. However, while remission rates did not differ between age groups, age was an independent predictor of non-adherence to adjusted treatment escalation guidelines: older patients were less likely to receive steroid sparing therapy after more than one course of oral prednisone or oral budesonide. Additional studies are necessary to determine the safest treatment regimen for this possibly frail population.